The effect of human settlement on the abundance and community structure of ammonia oxidizers in tropical stream sediments - Reis, Mariana P.; Ávila, Marcelo P.; Keijzer, Rosalinde M.; Barbosa, Francisco A. R.; Chartone-Souza, Edmar; Nascimento, Andréa M. A.; Laanbroek, Hendrikus J. (Frontiers in Microbiology, 2015)
Ammonia-oxidizing archaea (AOA) and bacteria (AOB) are a diverse and functionally important group in the nitrogen cycle. Nevertheless, AOA and AOB communities driving this process remain uncharacterized in tropical freshwater sediment. Here, the effect of human settlement on the AOA and AOB diversity and abundance have been assessed by phylogenetic and quantitative PCR analyses, using archaeal and bacterial amoA and 16S rRNA genes. Overall, each environment contained specific clades of amoA and 16S rRNA genes sequences, suggesting that selective pressures lead to AOA and AOB inhabiting distinct ecological niches. Human settlement activities, as derived from increased metal and mineral nitrogen contents, appear to cause a response among the AOB community, with Nitrosomonas taking advantage over Nitrosospira in impacted environments. We also observed a dominance of AOB over AOA in mining-impacted sediments, suggesting that AOB might be the primary drivers of ammonia oxidation in these sediments. In addition, ammonia concentrations demonstrated to be the driver for the abundance of AOA, with an inversely proportional correlation between them. Our findings also revealed the presence of novel ecotypes of Thaumarchaeota, such as those related to the obligate acidophilic Nitrosotalea devanaterra at ammonia-rich places of circumneutral pH. These data add significant new information regarding AOA and AOB from tropical freshwater sediments, albeit future studies would be required to provide additional insights into the niche differentiation among these microorganisms.